Information Needs Analysis For Inventory Management System Development Based On Existing Conditions In MSMEs - Jeremy Andrian Kurniadi; Yuanita Handayati (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
The purpose of this research is to strengthen its competitive advantage in the digital business industry in Indonesia by utilizing digital solutions to fulfill consumer needs, considering increasing market rivalry and the progress of digital products. The interview was conducted with micro, small, and medium-sized enterprises (MSMEs) located in West Java from January to June 2024 to identify the issues and needs of MSMEs. The identified problems need to be further processed using the System Development Life Cycle method. The results are expected to be utilized in the development of an Inventory Management Information System that can support the effectiveness of inventory management by MSMEs.